Organoid Culture Applications: Mini Systematic Review - Rilwan Efendi; Puti Khairunnajwa Amar; Resti Rahayu; Putra Santoso; Zozy Aneloi Noli; Rita Maliza (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Recent scientific developments in the stem cell field have made it possible to create complex organoids, or structures that resemble complete organs, in vitro. In the majority of these methods, stem cells produced from stem cells or tissue progenitors are allowed to self-organize into three-dimensional (3D) structures using culture systems in three dimensions. The purpose of this study is to ascertain the use of organoid culture in the area of health. This kind of study employs the literature review methodology. The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) criteria are referenced throughout the stages of the literature review performed in this study. The four processes that make up this level are identification, screening, eligibility, and acceptance. These discoveries showing that human stem cells and patient-derived pluripotent stem cells can be used to generate organoids open up a wide range of opportunities for modeling and disease development, toxicological research and medication discovery, and the field of regenerative medicine. Here, we discuss some of the most significant recent advancements in 3D human organoid production as well as the field's historical advancements. Finally, we discuss present restrictions and provide illustrations of how organoid technology may be used in the healthcare industry.